Public atttitude towards urban agriculture in Kano State, Nigeria - Liman, Mohammed (2016)
Urban settlement are planned and endowed with improved public amenities such as medical facilities, employments opportunities, education opportunities, improved households infrastructure, good roads network, electricity and many more. Based on this disparity, urban areas enjoy improved standard of living when compare to their rural counterparts which resulted to rural-urban migration usually in search of greener pasture. High concentration of people in the urban centre exerts untold pressure to the limited opportunities in the urban centres. As a result of that, despite these advantages enjoyed by the urban populace, when it comes to satisfying some basic household need such as food, the urban dwellers are at the disadvantage site. Food insecurity, unemployment and poverty have become the main feature of Kano state urban centres which is the largest State in Nigeria. Urban agriculture has proved to be a reliable solution to some of these problems in Kano state, however the extents to which the teeming populace are aware of health, social and economic benefits and the values of urban agriculture is not known. The objective of this study is to investigate public attitude towards urban agriculture in Kano State, Nigeria. A survey was conducted in Kano State, Nigeria with Gwale local government area in Zone A, Danbatta in zone B and Wudil local government area in zone C chosen for data collection. These local governments were selected from each of the senatorial districts by taking into consideration the level their urbanisation and the extent to which urban agriculture is practice. Using systematic random sampling, 585 households’ responds to 65 questions in structured questionnaire. Information on their knowledge and experience, personal norms, assigned values, held value and attitude were gathered. Assigned value model was applied in this study. Descriptive statistics, factor analysis and hierarchy regression were used to analysed the collected data. Descriptive statistics was employed to analysed age, gender, marital status, household size, education level and average income per-month of the respondents. Percentage, mean, standard deviation was used. Factor analysis was used to find those factors that shape public attitude towards urban agriculture in Kano State and the result revealed experience and knowledge, personal norms, individual safety and security (assigned value), individual benefits (assigned value) and held value as the dimensions of Respondents’ Attitude towards Urban Agriculture in Kano State. In addition, hierarchical regression was used to find the relationship between attitude and those factors shape it and also to look at moderating role of held value in that relationship, the results of the hierarchy regression show that experience and knowledge, Individual safety and security (assigned value) and individual benefits (assigned value) has significantly influence attitude towards urban agriculture in Kano State, Nigeria. Not only that held value has significantly moderate the relationship between Experience and knowledge, Individual safety and security (assigned value), individual benefits (assigned value) and attitude but does not moderate the relationship between personal norms and attitude. This shows the important role of held value as a moderator in the relationship between those factors and attitude. Having positive attitude towards urban agriculture will leads to the expression of this attitude in good behaviour towards it which will leads to greater participation in urban agriculture. With households having good knowledge and personal norms of urban agriculture, also having assigned both safety and economic values to this viable venture, it is recommended that Kano State government should change its current stand on urban agriculture which recognized only planting of trees to embrace other aspect of urban agriculture such ashorticulture and animal husbandry. By adopting it as policy option it will help in tackling the problems of food insecurity, unemployment and poverty in urban canters of Kano State which are the major problems confronting policy makers today.